2017
DOI: 10.1038/s41467-017-02014-0
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for TNA synthesis by an engineered TNA polymerase

Abstract: Darwinian evolution experiments carried out on xeno-nucleic acid (XNA) polymers require engineered polymerases that can faithfully and efficiently copy genetic information back and forth between DNA and XNA. However, current XNA polymerases function with inferior activity relative to their natural counterparts. Here, we report five X-ray crystal structures that illustrate the pathway by which α-(l)-threofuranosyl nucleic acid (TNA) triphosphates are selected and extended in a template-dependent manner using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(72 citation statements)
references
References 56 publications
1
70
0
1
Order By: Relevance
“…Recently, crystal structures of closed ternary complexes of KOD DNA pol [6] and a mutant [7] were published, giving first insights into the coordination of the triphosphate and the metal ions in the active site. However, structural data for DNA pols in complex with the above-mentioned nucleobasemodified nucleotides is so far only limited to the A-family KlenTaq DNA pol.…”
mentioning
confidence: 99%
“…Recently, crystal structures of closed ternary complexes of KOD DNA pol [6] and a mutant [7] were published, giving first insights into the coordination of the triphosphate and the metal ions in the active site. However, structural data for DNA pols in complex with the above-mentioned nucleobasemodified nucleotides is so far only limited to the A-family KlenTaq DNA pol.…”
mentioning
confidence: 99%
“…This dynamic process represents a key bottleneck in the engineering of XNA polymerases, where the unnatural triphosphate substrates (or XNA templates, or both) are likely to have suboptimal fit in the active site, as recently reported for a KOD-based TNA synthase crystallised as a ternary complex with a nascent DNA duplex and TNA nucleotide triphosphate in its active site [34].…”
Section: Bypassing Knowledge Gaps With Focused Libraries -The Second mentioning
confidence: 95%
“…Chim et al recently reported ternary structures of a hyperthermophilic B-family polymerase, an engineered KOD mutant, polymerizing TNA [152]. Given the prevalent use of B-family hyperthermophiles in polymerase engineering, the structures of the apo, binary, and ternary polymerase complexes will prove useful in developing hypotheses for further work in the field.…”
Section: Rational Engineering Of Xna Polymerases: Structural Insightsmentioning
confidence: 99%